Penerapan Program Pembelajaran Tata Rias Sehari-Hari Dengan Strategi Project Based Learning Pada Anak Dengan Hambatan Intelektual - Anelia Muanis; Oom Sitti Homdijah (Peneliti.net, 2023)
This research is motivated by the problems that exist in the field related to the readiness of students with intellectual barriers in facing the post-school world which requires students to have certain skills and talents. Before conducting the research, the researcher made observations at the school to find out whether the school had previously implemented cosmetology learning, the extent of the school's readiness to implement this program, the extent of the teacher's skills and the extent of students' interest in learning cosmetology skills. Based on these observations, the researcher found that the school already had good facilities, students' interest in learning cosmetology skills was high, but there were no teachers who had qualified competencies so that learning could not be implemented. Therefore the researchers created a daily cosmetology skills learning program -a day dedicated to teachers as facilitators in the implementation of learning and programs for students tailored to their needs by implementing a project based learning strategy. This program aims to enable students to apply makeup in simple forms that will be useful both in everyday life and in the post-school world. The method used in this research uses a mix method that combines quantitative and qualitative approaches with the research subject being 1 student at SMALB XI. Data collection techniques using tests. the data analysis technique uses descriptive statistics which are poured into graphs. The results of this study indicate that the application of the daily cosmetology skills program using the project based learning method is successful. This is evidenced by the results of the pretest and posttest which showed a significant increase.